2022
DOI: 10.1039/d2cp04174j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of limonene with the water dimer

Abstract: The interactions of two molecules of water with the terpene limonene are characterised by chirped-pulse Fourier transform microwave spectroscopy. Seven isomers of limonene-(H2O)2 have been observed, and identified from the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(132 reference statements)
1
3
0
Order By: Relevance
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
“…This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low-energy isomers of weakly bound complexes. 50,51,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high-confidence determination of the analyte absolute configuration.…”
Section: Discussionmentioning
confidence: 99%
“…11−13 The development of chirped pulse Fourier transform microwave (CP-FTMW) spectroscopy, 14 with the capacity of recording large sections of the spectrum at once, has further advanced the study of microsolvated complexes, revealing a wealth of species produced in supersonic jets. Recent reports include complexes with a large number of isomers, such as limonene-(H 2 O) 1,2 , 15,16 aggregates of various sizes between difluoromethane and water, 17 propiolactone-(H 2 O) 1−5 , 5 3-methylcatechol-(H 2 O) 1−5 , 18 22 Usually more than one isomer is observed for complexes with up to three waters. For higher-order hydrates, only one isomer was observed, except for β-propiolactone-(H 2 O) 4 , 5 for which two isomers were found.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several spectroscopic techniques across the electromagnetic spectrum have been applied to these investigations including microwave rotational, terahertz vibration–rotation, infrared ion dip, and ultraviolet hole burning, among others. Because of its high sensitivity to the spatial mass distribution, rotational spectroscopy has the unique advantage of being able to distinguish between close configurations (conformers and isomers), which makes it an extremely powerful technique for structural analysis. The development of chirped pulse Fourier transform microwave (CP-FTMW) spectroscopy, with the capacity of recording large sections of the spectrum at once, has further advanced the study of microsolvated complexes, revealing a wealth of species produced in supersonic jets. Recent reports include complexes with a large number of isomers, such as limonene-(H 2 O) 1,2 , , aggregates of various sizes between difluoromethane and water, and complexes with a large number of water molecules, such as β-propiolactone-(H 2 O) 1–5 , 3-methylcatechol-(H 2 O) 1–5 , 3-methyl-3-oxetanemethanol-(H 2 O) 1–6 , glycolaldehyde-(H 2 O) 1–6 , benzaldehyde-(H 2 O) 1–6 , and ethanolamine-(H 2 O) 1–7 . Usually more than one isomer is observed for complexes with up to three waters.…”
Section: Introductionmentioning
confidence: 99%